Medical online consultation service in gastroenterology at the University Hospital Zurich - Sabine Schmidt-Weitmann; Thomas Grischott; Peter Bauerfeind; Christiane Brockes (Cogent Medicine, 2017)
Background: Since 1999, the University Hospital Zurich (Switzerland) offers an e-mail based online consultation where patients can ask online doctors anonymous questions about individual health concerns. This study aimed at the characterization of the patient, the content of the question and the recommendations given specifically in the field of gastroenterology. Methods: In total, 3,489 inquiries were asked from July 2010 to December 2015. Based on the International Classification of Diseases ICD-10 and the Primary Care Code ICPC-2 252 (7.2%) inquiries were included in the retrospective qualitative study. The content of the requests was qualitatively evaluated by inductive categorization using a professional text analysis program (MAXQDA). Results: Of the users, 49.2% were male, 49.6% female. The mean age was 47.9 years. Main topics of the questions were bowel diseases in 29.8% (infectious in 6%, non-infectious in 7.1%, other bowel diseases in 16.7%). Most often patients suffered from abdominal pain (32.7%), diarrhea (22.7%), general weakness (22.7%) or epigastric pain (17.1%). Half (48.8%) of the questioners inquired about a second opinion while 25% asked for medical advice. The online doctors responded with detailed information about therapy (73.4%), explained a specific disease (63.9%) or provided decision support (13.9%). Most patients rated the clarity of the answer as good or very good (95.2%). Conclusion: An e-mail based teleconsultation in the field of gastroenterology can provide individual advice and empowers patients by improving their health literacy. Patients with bowel diseases have high expectations to obtain professional medical advice and need support in their decision-making process.